Upper critical field in a stoichiometric iron-based superconductor, CaKFe4As4 - Bristow, M; Coldea, A (University of Oxford, 2020)
These data are part of the manuscript (arXiv:2003.02888) entitled: "Competing pairing interactions responsible for the large upper critical field in a stoichiometric iron-based superconductor, CaKFe4As4". The data represent resistivity data collected at low temperatures and in magnetic fields up 16T using a superconducting magnet in Oxford as well as in pulsed fields up to 80T at the LNCMI in Toulouse, France. The measurements were performed between 2K and 300K either at constant temperature and varying the magnetic field or keeping the field constant and varying the temperature.